2022
DOI: 10.3390/s22197462
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Graph Routing Algorithm of Industrial Wireless Sensor Networks Using the Covariance-Matrix Adaptation Evolution Strategy

Abstract: The emergence of the Industrial Internet of Things (IIoT) has accelerated the adoption of Industrial Wireless Sensor Networks (IWSNs) for numerous applications. Effective communication in such applications requires reduced end-to-end transmission time, balanced energy consumption and increased communication reliability. Graph routing, the main routing method in IWSNs, has a significant impact on achieving effective communication in terms of satisfying these requirements. Graph routing algorithms involve applyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…Fig. 3 demonstrates that the best single-objective paths of the GR algorithm with a pre-set unequal clustering topology had a higher PDR and a lower PMR than the mesh topology in [1], which indicated that more data packets reached the . The proposed method facilitated a decrease in the ratio of missing data packets and an improvement in the communication reliability of the entire network.…”
Section: B Evaluation Results and Analysis 1) Network Reliability Eva...mentioning
confidence: 99%
See 4 more Smart Citations
“…Fig. 3 demonstrates that the best single-objective paths of the GR algorithm with a pre-set unequal clustering topology had a higher PDR and a lower PMR than the mesh topology in [1], which indicated that more data packets reached the . The proposed method facilitated a decrease in the ratio of missing data packets and an improvement in the communication reliability of the entire network.…”
Section: B Evaluation Results and Analysis 1) Network Reliability Eva...mentioning
confidence: 99%
“…The deficiencies of using single-objective paths for Graph Routing in an IWSN mesh topology were presented in [1]: unbalanced energy consumption leading to hotspots; low coverage; short lifetime of the network among others. To address these challenges, the proposed method principally evaluates best single-objective paths using pre-set unequal clustering.…”
Section: The Proposed Methodsmentioning
confidence: 99%
See 3 more Smart Citations